Seroprevalence of Chagas disease in urban and rural indigenous populations of the south of Gran Chaco - Colussi, Carlina Leila (2022)
Background: In Latin America, Chagas disease is endemic, with a high prevalence in rural indigenous communities and an increasing prevalence in urban areas owing to migration from rural areas with active vector transmission. This study aimed to assess differences in the prevalence of Chagas disease in urban and rural moqoit communities, one of the main ethnic indigenous groups in the south of Gran Chaco. Methods: A seroprevalence study was conducted in six moqoit populations in the Santa Fe province, Argentina. The variables studied were serology results for Chagas disease, residents of urban or rural areas, age, and sex. Results: The results showed that 9.26% of the 702 volunteers evaluated and 18.32% of the 131women of childbearing potential were seropositive. According to the calculated prevalence ratio, the prevalence of Chagas disease in urban communities was6.41 (95% confidence inverval: 3.73-11.02) times higher than that in rural communities: 21.59% in urban communities vs. 3.37%in rural communities. Conclusions: The seroprevalence found in the moqoit community was higher than the estimated level for the general population of the same region, with a greater impact in urban areas than in rural areas. The urbanization of groups of people with poor socio-sanitary conditions in the second half of the 20th century could have caused this higher seroprevalence of Chagas disease.